An Echo of Silence: A Comprehensive Research on Early Child Marriage in Iran - Ahmady, Kameel (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The purpose of this research was to recognize and identify the reasons for the prevalence of early child marriage in Iran and to analyze the social and cultural details of this social problem. Method: The current research method was integrated (qualitative-quantitative) and practical in terms of its purpose. In the qualitative part, the participants included adults, children and adolescent girls and boys who were married at a young age (under 18 years) for various reasons, who were selected by purposeful sampling. The research tool was an interview and continued with 311 participants far more then theoretical saturation were needed. For the validity of the findings, face validity and reliability were used with recoding method by the coding team. In the quantitative part of the research, it was based on the analysis of surveys conducted from 2006- 2014 in seven provinces (Khorasan Razavi, East Azerbaijan, Khuzestan, Sistan and Baluchistan, West Azerbaijan, Hormozgan and Isfahan) of the country. Results: The findings showed that the most important factors affecting the continuation of child marriage include poverty, low education and illiteracy, legal permission to marry (13 for girls and 15 for boys), social pressures, patriarchal views, and traditional and religious beliefs. One of the effects of early marriage is the increase in divorce, lack of Jobs and eduction, and child widowhood, the growth of orphaned and poorly cared for children, sexual abuse of girls, the continuation of the cycle of poverty and prostitution, and the increase in physical, sexual and mental illnesses for girls. Conclusion: Early marriage of female children and adolescents in Iran is prevalent as a social and cultural harm in most provinces of the country, which is associated with various harms. Therefore, there is a serious need for changing the current laws on marriage and the officials and those involved in the family field to take preventive and interventionist measures on this issue.